Health-Related Quality of Life and Cancer-Related Symptoms During Interdisciplinary Outpatient Rehabilitation for Malignant Brain Tumor. (December 2017) - McCarty, Stacy; Eickmeyer, Sarah M.; Kocherginsky, Masha; Keeshin, Susan; Shahpar, Samman; Semik, Patrick; Wong, Alex W.K.
Abstract : Objective: The aim of the study was to determine the relationships between functional outcomes, clinical symptoms, and health-related quality of life among patients with malignant brain tumors receiving interdisciplinary outpatient rehabilitation. Design: A prospective study of 49 adults with malignant brain tumors participating in outpatient therapies was performed. Outcome measures included the Functional Assessment of Cancer Therapy-Brain (FACT-Br) for health-related quality of life and the Patient-Reported Outcome Measures Instrument Survey (PROMIS) Depression and Pain Behavior scales measured at admission, discharge, 1 and 3 mos after discharge. Day Rehabilitation Outcome Scale (DayROS), a functional measure, was measured at admission and discharge. Results: The FACT-Br scores, PROMIS pain, and PROMIS depression scores did not significantly change. There were many negative associations seen between FACT-Br and PROMIS depression (all P < .0001) and less associations with PROMIS pain. There was a positive correlation between Day Rehabilitation Outcome Scale and FACT-Br ( P = .0058) and a negative association with PROMIS pain ( P = .028), but not with PROMIS depression. There were no correlations between Day Rehabilitation Outcome Scale gains and change in PROMIS depression, FACT-Br total, or PROMIS pain. Conclusions: Health-related quality of life, pain, and depression did not worsen. Patients who reported less depression and pain had better reported health-related quality of life. Level of function was also associated with HRQOL and pain, but not depression. Abstract : Supplemental digital content is available in the text.